(untitled) (Journal of the College of Basic Education, 2022)
If we wanted to apply the subject (acceptance) as a problematic cultural concept to one of the purposes of poetry, we would find that the purpose of pride is the most in the field to embrace the concept from outside it through what pride has on the conscience of the audience.